(untitled) (Scientific journal of the Fergana State University, 2024)
This article talked about the concept of phraseologism, its development and importance. Also, the use of expressions in English and Uzbek languages, their characteristics, similarities and differences were also explained. In addition, valuable sources that have a great place in Uzbek and English linguistics and brief comments on them were also given. In addition, this article suggested the problems that arose in the process of translating phraseological units in two languages and effective solutions to them. The benefits of comparing two languages to language learners and nations were also highlighted.